The fair share for rural life - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
FIARA 2000, Senegal s international fair for agriculture and animal resources was held in Dakar over 11 days in mid-December 1999